The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/j.ijthermalsci.2007.01.032
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of lumped capacitance approaches for the numerical prediction of heat and mass transfer in desiccant airflow systems

Abstract: In the present work, a detailed model of simultaneous heat and mass transfer through a desiccant micro-porous medium of a channel wall of compact heat and mass exchangers, such as desiccant wheels, was developed. The relevant phenomena considered by this model within the porous medium are surface diffusion of the adsorbed water, Knudsen diffusion of water vapour, heat conduction and the sorption process. A onedimensional formulation of this model is used to investigate the validity of two simplifying approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…(1) Humid air is the mixture of an ideal gas, and Dalton's law of partial pressures is true [35]. (2) One-dimensional transient heat and mass transfer are considered [36].…”
Section: Governing Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Humid air is the mixture of an ideal gas, and Dalton's law of partial pressures is true [35]. (2) One-dimensional transient heat and mass transfer are considered [36].…”
Section: Governing Equationmentioning
confidence: 99%
“…In order to understand performance of dehumidifier, it is necessary to consider effects of component operation in a transient state. Ruivo et al [35], based on the lumped-capacitance method used a one-dimensional formulation to investigate the validity of two simplifying approaches of neglecting the transversal heat and mass transfer resistance within the porous medium and cancelling only the thermal resistance on desiccant wheel. They showed that the Biot number for surface diffusion is several orders of magnitude higher than the corresponding thermal Biot number.…”
Section: Introductionmentioning
confidence: 99%
“…where D s is the surface diffusivity, and calculated by [30][31][32], q d is the density of the desiccant particle, and C w is the moisture content of the desiccant. D 0 is a constant that depends on the adsorbent and b depends on the type of adsorption bond.…”
Section: Moisture Transport In Desiccant Feltmentioning
confidence: 99%
“…They also discussed the effect of some practical issues such as wheel purge, residual water in the desiccant and the wheel supporting structure on the wheel performance. Ruivo et al [14] developed 1D transient heat and mass transfer model for desiccant wheel and presented two approaches. In the first approach, the model was valid for thickness lower than 0.1 mm, neglecting the transversal heat and mass transfer resistance in micro porous desiccant while in the second approach, the model was valid for thickness lower than 5 mm, neglecting only thermal resistance.…”
Section: Introductionmentioning
confidence: 99%